PRAKTEK OUTSOURCING DI BUMN PERSPEKTIF EKONOMI SYARIAH - Dwiyana Tohara Tohara (UIN Siber Syekh Nurjati Cirebon, 2016)
Abstract (Working is a duty of every man, by working a man earns money in order to fulfill the needs of his family and himself. By working and earning wages, human being is able of enforcing body, close the ' Awrah, and being able to worship to God Almighty.Outsourcing system is a working system which contains tripartite relationship between corporate employer (principal), outsourcing company (vendor), and workers/laborers. This system is derived from the mechanisms of Labor Market Flexibility (LMF) that actually addressed the proscons by various circles because it is considered as a new form of modern slavery.Based on theresults of several studieson the themeof outsourcingthathave been conductedamongacademic, this articlewillprovideacademicconclusionsrelated tothe practice of outsourcinginIndonesiafrom the perspective ofIslamic economics). Keywords : Outsourcing Practice, Labor, Islamic Economy, Fair WagesÂ Abstrak(Bekerja adalah kewajiban setiap manusia, dengan bekerja seseorang menghasilkan uang untuk memenuhi kebutuhan keluarganya dan dirinya sendiri. Dengan bekerja dan mendapatkan upah, manusia mampu menegakkan kehormatan dan mampu ibadah kepada Allah SWT.Sistem outsourcing adalah sistem kerja yang berisi hubungan tripartit antara majikan perusahaan (principal), perusahaan outsourcing (vendor), dan pekerja / buruh. Sistem ini berasal dari mekanisme Tenaga Kerja Market Flexibility (LMF), yang pembahasannya menimbulkan pro kontra oleh berbagai kalangan karena dianggap sebagai bentuk baru perbudakan modern.Berdasarkan hasil kajian beberapa penelitian pada tema outsourcing yang telah dilakukan oleh para akademisi, artikel ini akan memberikan kesimpulan akademis yang berhubungan dengan praktek outsourcing di Indonesia dari perspektif ekonomi Islam).(11 pt Times New Roman italic)Keywords : praktek outsourcing, Pekerja, Ekonomi Islam, Upah layak